Comparing Agrarian Mythologies and Rituals: Adyghe and Anatolian Fertility Cults and Their Role in Ancient Eurasian Symbolic Transmission - Kagazezhev, Zhiraslan V. (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study explores the symbolic and ritual parallels between the agricultural and fertility cults of the Adyghe people and the religious practices of ancient Anatolian civilisations, particularly the Hatti and Hittites. The research aims to demonstrate that Adyghe spiritual traditions are not isolated but form part of a broader Eurasian religious continuum shaped by cultural diffusion and shared cosmological archetypes. Using a qualitative, historical-comparative approach, the study analyses mythological narratives, ritual texts, linguistic terms, and archaeological records drawn from both Adyghe ethnographies and translated Hittite sources. The findings reveal striking similarities: the thunder god who defeats serpent-like forces, the symbolism of sacred trees and animal skins, and springtime fertility rites aligned with agricultural renewal. These elements suggest a structural continuity in agrarian cosmology across regions and epochs. The research contributes to the study of indigenous religions and ecospirituality by highlighting how local rites preserve ancient symbolic systems and maintain environmental ethics rooted in spiritual cosmology. The originality of this study lies in its cross-cultural synthesis and structural comparison of ritual motifs, which uncovers historical and theological connections between the Adyghe and Anatolian traditions—an area largely overlooked in prior scholarship. By bridging cultural histories of the Caucasus and Anatolia, the study provides new insights into the transregional development of religious thought within ancient agrarian societies.